Prognostic Significance of the Epithelial–Mesenchymal Transition Phenotype in Basal Cell Carcinoma: A Meta-Analysis of E-Cadherin Loss and Stromal Alpha-SMA Upregulation as Recurrence Predictors - Meira Astuti; Endang Mahati; Udadi Sadhana; Selamat Budijitno; Ign Riwanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Basal cell carcinoma represents the most prevalent cutaneous malignancy worldwide. While metastasis is rare, local recurrence poses a substantial therapeutic challenge, particularly in the anatomically critical H-zone of the face. Conventional risk stratification relies on tumor size and histological subtype, but these markers frequently fail to capture the intrinsic biological aggressiveness of the tumor. The epithelial–mesenchymal transition phenotype, characterized by the loss of epithelial adhesion molecule E-cadherin and the activation of the tumor stroma via alpha-smooth muscle actin expression, has emerged as a potential driver of local invasion. Methods: We conducted a systematic review and meta-analysis adhering to PRISMA 2020 guidelines to evaluate the prognostic value of these biomarkers. A comprehensive search identified ten pivotal studies comprising 648 cases. The primary endpoint was adverse outcome, defined as clinical recurrence or the presence of high-risk infiltrative histology. Data were synthesized using a random-effects model to calculate pooled Odds Ratios and Standardized Mean Differences, with rigorous sensitivity analyses to account for heterogeneity. Results: The meta-analysis revealed a profound association between stromal activation and adverse outcomes. Alpha-SMA upregulation was the most robust predictor, with a pooled Odds Ratio of 6.82 (95% CI: 3.14–14.81; p < 0.0001). Loss of membranous E-cadherin also significantly predicted recurrence (Odds Ratio = 4.15; 95% CI: 1.89–9.10; p = 0.0004), although with higher heterogeneity, reflecting the focal nature of partial epithelial–mesenchymal transition at the invasive front. The combined phenotype of high alpha-SMA and low E-Cadherin represented the highest risk profile. Conclusion: The epithelial–mesenchymal transition phenotype serves as a high-fidelity predictor of basal cell carcinoma recurrence. Stromal alpha-SMA marks a permissive soil for invasion and should be considered for integration into pathological reporting for ambiguous or high-risk tumors to guide surgical margin management.